Evaluasi Efektivitas Sistem Pengendalian Internal Perusahaan Studi Pada CV Permata Agro Mandiri di Kota Batu - Farandi, Alfin Dafa Hans; Djaelani, Abdul Kodir; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to evaluate the effectiveness of the internal control system implemented by CV Permata Agro Mandiri, a micro, small, and medium enterprise (MSME) based in Batu City that specializes in processing apples into local souvenir products. The evaluation is based on the five components of the COSO internal control framework: control environment, risk assessment, control activities, information and communication, and monitoring. A qualitative descriptive method was employed, using in-depth interviews, observation, and documentation techniques. The results show that the internal control system at CV Permata Agro Mandiri is generally effective. The company has a clear organizational structure and division of tasks, and it performs routine monitoring through weekly performance evaluations. However, several weaknesses were identified, such as the lack of formal documentation, the absence of A structured internal audit system, and informal inter-departmental communication. On the other hand, the company demonstrates strong compliance with regulations and product legality requirements by participating in training programs held by government agencies and consistently implementing standard operating procedures (SOPs). Keywords: Internal Control System, Effectiveness, COSO, Msmes, CV Permata Agro Mandiri, Qualitative Research.